Al-Zubair City: The argument of Identity - A Cultural Study - Nasir Rahai, Prof. Dr. Qais (Basra studies journal, 2026)
This study examines Zubair from a cultural studies perspective, analyzing complex identity transformations over four centuries. Its main question is: How was Zubair's identity shaped amid successive migrations and political-economic transformations? Using cultural analysis tools, the study explores how sixteenth-century Najdi migration formed the city's cultural identity core, evolving through Ottoman rule, British occupation, and the modern Iraqi state. It analyzes cultural-sectarian conflicts, 1920s separatist attempts, and radical demographic transformations in the twentieth century's second half. The study employs theoretical concepts from Pierre Bourdieu (habitus, symbolic violence),). It concludes that Zubair's identity is not fixed but continuously negotiated, and that demographic transformations led to the Najdi habitus's disintegration and emergence of a multi-spectrum city identity.